CHANGES IN BACTERIAL VOLUME AS THE RESULT OF SPECIFIC AGGLUTINATION - Jones, F. S. (The Rockefeller University Press, 1933)
Measurements indicate that bacterial antigens increase in volume as the result of specific agglutination. There is a general parallelism between the increase in antigenic volume and the concentration of the immune serum. The phenomenon is specific. There is no increase with normal serum; with absorbed serum the increase is slight and it can be correlated with the presence of unabsorbed antibody. The effect is enduring as shown by volumetric determinations upon repeatedly washed, agglutinated bacteria.